A cross-cultural study on pragmatic transfer in compliment responses by learners of English at Hung Vuong University - Nguyễn, Thị Tố Loan (ĐHNN, 2017)
It is a tendency that L2 speakers exhibit the impact of their native language and culture on their acquisition and performance of an additional language. Therefore, transfer of L1 pragmatic transfer is an appealing subject to study.